Clinical Predictors of Minimal Extrathyroid Invasion of Papillary Thyroid Cancer - Pavlo Lishchynskyi; Volodymyr Palamarchuk; Oleh Mazur; Volodymyr Kuts; Sergii Zemskov; Oleksandr Tovkai; Olexii Dronov (Bogomolets National Medical University, 2022)
extrathyroidal invasion (ETI) of papillary thyroid cancer (PTC) is a risk factor for locoregional metastasis. The clinical significance of minimal ETI depending on the primary tumor size has not been studied thoroughly. The combination of tumor diameter and minimal ETI can be used as a reliable prognostic factor for persistence of the disease. Given that the identification of the minimal ETI is possible only during the final histopathological study, there is a need to assess the existing preoperative clinical predictors that increase the probability of minimal ETI of PTC. The aim of the study is to assess preoperative clinical predictors that increase the probability of minimal extrathyroidal invasion of papillary thyroid cancer. A retro-prospective single-center study of preoperative clinical predictors that increase the probability of extrathyroidal invasion of thyroid cancer was conducted. Data from 514 patients aged 5 to 81 years were processed. Patients underwent surgery for papillary thyroid cancer for the first time. Scope of the operation: extrafascial thyroidectomy. Central neck dissection. Lymphadenectomy. All patients had clinical signs of low risk of recurrence. The mean age of patients was 44.4 ± 14.5 years. There were 91 men (17.7%) and 423 women (82.3%). Patients were divided into two groups: group 1 with 169 patients with minimal extraorganic invasion aged 5 to 71 years, group 2 with 345 patients without invasion aged 10 to 81 years. The following features were taken into account for the analysis: 1) age of patients; 2) their sex; 3) the size of the dominant tumor. The results were statistically processed using a specialized statistical program StatPlus Pro v.7 (AnalystSoft Inc.) and Epitools statistical calculators (Ausvet, https://epitools.ausvet.com.au/). According to the results, both by age (mean age of patients in group 1 - 44.7 ± 14.4 years; mean age of patients in group 2 - 44.3 ± 14.6 years) and by sex (in group 1 - 30 men (17.8%), 139 women (82.2%), in group 2 - 61 men (17.7%), 284 women (82.3%), the groups were almost identical, both groups were significantly (p <0.01) dominated by women. The size of the primary tumor in group 1 - 15.0 (10.0; 20.0) mm - was statistically significantly higher (p <0.001) than in the second - 10.0 (7.0; 15.0) mm. Most of patients (71.0%) with invasion had a primary tumor size > 10 mm, while in group 2 there were only 42.6% of such patients. Within the size ranges up to 10 mm, the probability of detection of invasion is 14.0% - 21.6%, while within the size ranges over 10 mm, it may be 41.9% - 50.0%. A tumor size of PTC over 10 mm, with a diagnostic strength of 61.9%, increases the risk of minimal extrathyroidal invasion. The average size of the primary tumor in the group of patients with minimal ETI is 15.0 (10.0; 20.0) mm, which is statistically significantly higher (p <0.001) than the same value in the group of patients without EIT - 10.0 (7.0; 15.0) mm.  In patients with a PTC tumor size of less than 10 mm, the probability of minimal ETI ranges from 14.0% to 21.6%, while the probability of minimal ETI in patients with a tumor size over 10 mm ranges from 41.9% to 50.0%. Given that minimal ETI may be one of the factors of increased risk of PTC locoregional metastasis, surgery for PTC patients with a tumor size over 10 mm should be supplemented with central neck dissection, lymphadenectomy. A tumor size of PTC over 10 mm, with a diagnostic strength of 61.9%, increases the risk of minimal extrathyroidal invasion, which is also an argument in favor of central neck dissection, lymphadenectomy during surgery for patients with tumor size over 10 mm. The patients' age and sex cannot be the factors that increase the risk of minimal extrathyroidal invasion of papillary thyroid cancer.